The cunning of stupidity - Noam Yuran (Finance and Society, 2020)
Exploring the historical imagination that surfaces at the time of crisis, Samman contributes to the effort to conceive of financial capitalism as a more or less distinct political, social and cultural era. The question that remains is how the narrative tropes he explores are related to finance in its narrower sense. Why does historical imagination wear these specific forms in financial times?
Keywords: 300